EFFECTIVENESS OF MUROTTAL THERAPY ON BABIES’ WEIGHT CHANGES - Syamsuriyati Syamsuriyati; Rika Handayani; Sutrani Syarif; Ani T Prianti; A. Ummu Salmah; Syamsuar Manyullei; Risnah Risnah; Muhammad Irwan (Universitas Islam Negeri Alauddin Makassar, 2020)
Many newborn babies have a low weight, it has a bad impact in the process of growth and development.Murottal is a recording of the sound of the Qur'an which is sung by a qori . Murotal therapy performed for several minutes or hours in a voice that sounds good can give a sense of comfort for the body to move up to be able to raise the baby's weight. The Purpose Of This Research Is To Know The Murottal Effects Of Changes In Baby Weight. This research is quasi experimental pre-test post test kontrol group design. Samples in this study A total of 44 newborn babies, divided into two groups consisting of 22 respondents, namely the Intervention Group and the Control Group. The Intervention Group received treatment hearing murottal therapy and the control group did not receive treatment. Using the Mann Whitney statistical test. The results of the study with the Mann Whitney Statistical Test p: 0.630> 0.05. This means that there is no average difference between the weight of infants in the intervention group and the control group. However, it only gave a change, by showing that the weight of the intervention group infants after being given a treatment was lower in body weight compared to the control group which was 2,577 grams, whereas in the control group without being treated there was more weight loss than the intervention group which was 2,750 grams. Murottal therapy has not changed statistically but there has been a change in the mean and standard deviation, so it is recommended that mothers apply Murottal therapy during the breastfeeding process using appropriate Standard operating procedures.